Two men holding drinks - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two men posing together. The man on the right has his right arm around the second man. He is wearing a light-colored sweater and three necklaces. The man on the left has his left arm around the first man. He is wearing a dark-colored sweater with a possible name tag stuck to it, and a tie. He has a drink in his right hand.